The Influence Of Personnel Development And The Quality Of The Working Atmosphere On The Performance Of Employees Is Mediated By The Satisfaction Of The Career Ladder - Wijaya, Juliyans Purnama Putra; Ariadi, Gede (Universitas Muhammadiyah Pontianak, 2026)
This study examines the influence of personnel development and work atmosphere quality on employee performance, with career satisfaction as a mediating variable at PT Indo Sakura Indah. The research aims to analyze direct and indirect relationships among these variables. A quantitative approach was employed using SEM-PLS with SmartPLS 3.0 on data collected from 113 production employees. The results indicate that personnel development significantly affects career satisfaction but not employee performance directly, while work atmosphere quality significantly influences both career satisfaction and performance. Career satisfaction affects performance but does not mediate the relationships. These findings highlight the importance of a conducive work environment and targeted development programs.